Profile of High School Students' Problem-Solving Skills and the Application of Problem-Based Learning: A Preliminary Study - Abdul Ghofur; Budi Jatmiko; I Gusti Made Sanjaya (Indonesia Approach Education, 2023)
This study's purpose is to obtain a profile of students' problem-solving skills and describe the achievement of implementing Problem-Based Learning (PBL) in high schools. The profile of problem-solving skills was obtained by giving tests and questionnaires to 53 students, while the achievement of implementing the PBL model was obtained by interviewing six students and one chemistry teacher. The research data obtained is then described. The findings revealed that the students' problem-solving skills remained low, namely in the poor and very poor categories with a percentage of 67.93%. Meanwhile, students' problem-solving skills were in the enough category at 20.75%, in the good category at 11.32%, and in the very good category were not found. This study also demonstrates that the teacher's application of learning with the PBL has yet to lead to students achieving the problem-solving skill indicators that are measured. In addition, students' prior knowledge was found to have contributed to the achievement of these indicators. This study suggests adapting and modifying the PBL model's syntax based on all present constraints to develop a new learning model capable of appropriately training students' problem-solving skills by focusing on the side of students' prior knowledge, formulation hypothesis, and reflection activities in learning.